3,4,5-Trihydroxy-N '- (1-methyl-1H-indol-2-yl)methylidene benzohydrazide - Khaledi, H.; Abdulla, M.A.; Robinson, W.T.; Ali, Hapipah Mohd; Saharin, S.M. (International Union of Crystallography, 2009)
The structure of the title compound, C17H15N3O4, displays intermolecular O-H center dot center dot center dot N and O-H center dot center dot center dot O hydrogen bonding between adjacent molecules. Intramolecular O-H center dot center dot center dot O hydrogen bonds also occur. The molecule is essentially planar with a deviation of 0.090 (1) angstrom from the best plane running through the connected ring systems.